Resting-State Functional Network Topology Alterations of the Occipital Lobe Associated With Attention Impairment in Isolated Rapid Eye Movement Behavior Disorder - Geng, Chaofan; Wang, Shenghui; Li, Zhonglin; Xu, Pengfei; Bai, Yingying; Zhou, Yao; Zhang, Xinyu; Li, Yongli; Zhang, Jiewen; Zhang, Hongju (Frontiers in Aging Neuroscience, 2022)
Purpose: This study investigated the topological properties of brain functional networks in patients with idiopathic rapid eye movement sleep behavior disorder (iRBD). Participants and Methods: Twenty-one patients with iRBD (iRBD group) and 22 healthy controls (HC) were evaluated by the neuropsychological measures in cognitive and motor, and were performed by resting-state functional magnetic resonance imaging(rs-fMRI). Rs-fMRI data were analyzed using graph-theory, including small-world properties, network efficiency, network local efficiency, nodal shortest path, the node efficiency, and network connectivity, as well as the correlation between behavioral characteristics and altered brain topological features. Results: iRBD patients showed significant decrease scores in ROCFT-copy, SDMT, AVLT-N1, AVLT-N2, AVLT-N3 and AVLT-N1-3, and increase scores in TMT-A, TMT-B and UPDRSIII than in HC (p < 0.05). Compared with the HCs, iRBD patients had no difference in the small-world attributes (p > 0.05). However, there were significantly decrease in network global efficiency (p = .0052) and network local efficiency (p = 0.0146), nevertheless increase in characteristic path length (p = .0071). There were lower nodal efficiency of occipital gyrus and nodal shortest path which in frontal, parietal, temporal lobe and cingulate gyrus. Functional connectivities were decreased between the nodes of occipital with the regions where had declined nodal shortest path. There was a significant positive correlation between TMT-A scores and nodal efficiency of right middle occipital gyrus (R= .602, p= .014). Conclusion: These results suggest that abnormal behaviors may be associated with disrupted brain network topology and functional connectivity in iRBD patients, and also provide novel insights to understand pathophysiological mechanisms in iRBD.